Avalia????o dos aspectos bioqu??micos e morfol??gicos da a????o do laser de baixa pot??ncia em camundongos mdx submetidos ao exerc??cio de alta intensidade - Silva, Andr??ia Aparecida de Oliveira (2014)
This study aims to determine whether the therapy of low intensity laser (LLLT) can alter biochemical, functional and morphological parameters in mdx subjected to high intensity exercise on the treadmill mice. And 21 mice used C57BL/10ScSn-Dmdmdx/J C57BL/10ScSn 7 mice, all aged 4 weeks. The animals were divided into 4 groups: a control group n=7 C57BL/10 (C57BL Control); second set mdx control n=7 (mdx control), third group mdx fatigued n= 7 underwent forced high-intensity exercise on a treadmill (mdx fatigue); fourth group mdx n=7 with the same characteristics, but were treated with LLLT AsGaAl DMC ?? brand Model Photon Laser III, power 30mW, wavelength ?? 808nm, 9J energy a total single point on the gastrocnemius muscle hind paw (mdx LLLT) for three days consecutive before exercise, blood samples were taken immediately after exercise and euthanasia (24h after). Blood samples from mdx mice LLLT showed significantly higher levels of markers of oxidative stress than mice "C57BL control" and LLLT reduced the activity creatine kinase and protein carbonyls, even in conditions of muscle fatigue. The activities of the antioxidant enzyme superoxide dismutase (SOD) were higher in mdx than in C57BL. The LLLT also significantly reduced the level of this marker. LLLT has beneficial effects on the skeletal muscle of mdx animals, improving the performance of these animals. The application of LLLT and dose parameters used in this study was not able to change the morphology of the dystrophic muscle.